Congenital hyperinsulinism and glycogenosis-like phenotype due to a novel HNF4A mutation. (April 2017) - Stanik, Juraj; Skopkova, Martina; Brennerova, Katarina; Danis, Daniel; Rosolankova, Monika; Salingova, Anna; Bzduch, Vladimir; Klimes, Iwar; Gasperikova, Daniela
Highlights: Novel HNF4A gene mutation caused CHI and glycogenosis-like phenotype. Adult mutation carriers had MODY diabetes. Mutation carriers benefited from the personalized therapy. WES is an appropriate method for testing of patients with unclear CHI phenotype. In patients with CHI and hepatopathy, HNF4A analysis may be considered prior WES. Abstract: Aim: Congenital hyperinsulinism (CHI) and glycogen storage disease (glycogenosis) are both causing hypoglycemia during infancy, but with different additional clinical features and therapeutic approach. We aimed to identify a genetic cause in a child with an ambiguous phenotype. Methods and results: We present a child with hyperinsulinemic hypoglycemia, physiological 3-OH butyrate, increased triglyceride serum levels, increased level of glycogen in erythrocytes, increased liver transaminases, and increased echogenicity on liver ultrasonography. As both parents of the proband were referred as healthy, we raised a clinical suspicion on glycogenosis with recessive inheritance. However, whole exome sequencing revealed no mutation in genes causing glycogenosis, but a novel heterozygous variant LRG_483t1: c.427-1G > A in the HNF4A gene was identified. Aberrant splicing resulting in in-frame deletion c.429_476del, p.(T144_I159del) was confirmed by sequencing of HNF4A transcripts reverse-transcribed from whole blood RNA. The same variant was found in five of eight tested family relatives (one of them already had diabetes, two had prediabetes). With regard to the results of DNA analysis, we added diazoxide to the therapy. Consequently, the frequency and severity of hypoglycemia in the proband decreased. We have also recommended sulfonylurea treatment after diabetes onset in adult mutation carriers. Conclusions: We have identified a novel HNF4A gene mutation in our patient with CHI and glycogenosis-like phenotype. The proband and her family members benefited from the genetic testing by WES method and consequently personalized therapy. Nevertheless, the HNF4A gene testing may be considered in selected CHI cases with glycogenosis-like phenotype prior WES analysis.